PENGARUH DEBT DEFAULT, PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, OPINION SHOPPING, OPINI AUDIT TAHUN SEBELUMNYA TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Rista Uly; Anita Wahyu Indrasti (Universitas Budi Luhur, 2020)
The purpose of this study was to determine the effect of debt default, profitability, company growth, shopping opinion and previous year's audit opinion on going concern audit opinion. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2014 – 2017. The analytical technique used is logistic regression analysis using SPSS 21.0. From the research results prove that debt default, company growth and opinion shopping have no effect on going concern audit opinion, profitability has a negative effect on going concern audit opinion, and the previous year's audit opinion has a positive effect on going concern audit opinion